2018
DOI: 10.1038/s41598-017-19088-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among land surface temperature and LUCC, NDVI in typical karst area

Abstract: Land surface temperature (LST) can reflect the land surface water-heat exchange process comprehensively, which is considerably significant to the study of environmental change. However, research about LST in karst mountain areas with complex topography is scarce. Therefore, we retrieved the LST in a karst mountain area from Landsat 8 data and explored its relationships with LUCC and NDVI. The results showed that LST of the study area was noticeably affected by altitude and underlying surface type. In summer, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
111
2
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(136 citation statements)
references
References 27 publications
(30 reference statements)
11
111
2
12
Order By: Relevance
“…Additionally, seasonality, time of the day, and research methods are also aspects that can influence the accuracy of extracting LST [16]. Moreover, planned and traditional cities have different urban structures, which also impacts the LST [17]. Controlling the LST in the central area is crucial for people's health, living environment, and sustainable development.…”
mentioning
confidence: 99%
“…Additionally, seasonality, time of the day, and research methods are also aspects that can influence the accuracy of extracting LST [16]. Moreover, planned and traditional cities have different urban structures, which also impacts the LST [17]. Controlling the LST in the central area is crucial for people's health, living environment, and sustainable development.…”
mentioning
confidence: 99%
“…By comparing LST and NDVI maps, it shows that regions with the lowest NDVI values have the highest LST values. This may be a result of land-use change that exposes the earth's surface in those areas [51,59]. A spatial distribution map of SMI (in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, decline in the frequency of cloudy days is mostly linked to an increase in sunshine (i.e., lower incoming shortwave radiation compared to outgoing longwave radiation) and, in turn, more warming. In the literature, several works have indirectly assessed the performance of LST by linking it with some key climatic and environmental variables which could have a strong influence on air temperature (e.g., solar radiation) (e.g., [25,28,62]). However, these studies demonstrated that the association between the LST and these variables can vary considerably over space in response to the dominant local characteristics (e.g., land use).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the MODIS LSTs are calibrated for atmospheric interference in NASA labs. Due to their simplicity and robustness, LST products retrieved from MODIS Terra and Aqua have increasingly been used in different research applications (e.g., [25,28,32,41,[57][58][59][60][61][62]). In this study, daytime and nighttime surface temperatures were extracted from the Aqua LST 8-day composite product (MYD11A2V.6) for the Egyptian territory for the period from July 2002 to June 2015.…”
Section: Modis Lst Datamentioning
confidence: 99%